Textbooks for teaching the sociology of religion. Issue 2 (3rd April 2019) - Day, Abby
ABSTRACT: The sociology of religion, a vibrant sub-discipline of sociology, is popular amongst students taking degrees in Sociology, Theology, and Religious Studies. Teachers are often not sociology specialists and seek a standard text to help with classes. Others, who specialise in sociology, have usually no background in the study of religion. His review surveys the field of books recommended by teachers and students and finds few to wholly recommend. The author calls for texts to be more inclusive, less dogmatic, and more directed to best pedological practice.